Prenatal risk factors for kidney and urinary tract anomalies - Mak, Robert; Schaefer, Franz (Nature reviews. Nephrology, 2014)
Childhood-onset chronic kidney disease is the result of congenital anomalies of the kidneys and urinary tract in approximately two-thirds of all patients. An area of intense research in recent years, however, is the potential impact of maternal obesity on renal ontogenesis or postnatal renal function in the offspring.